2021
DOI: 10.1002/anie.202108313
|View full text |Cite
|
Sign up to set email alerts
|

A Metal–Organic Framework derived CuxOyCz Catalyst for Electrochemical CO2 Reduction and Impact of Local pH Change

Abstract: Developing highly efficient and selective electrocatalysts for the CO 2 reduction reaction to produce valueadded chemicals has been intensively pursued. We report as eries of Cu x O y C z nanostructured electrocatalysts derived from aC u-based MOF as porous self-sacrificial template. Blending catalysts with polytetrafluoroethylene (PTFE) on gas diffusion electrodes (GDEs) suppressed the competitive hydrogen evolution reaction. 25 to 50 wt %t eflonized GDEs exhibited aF aradaic efficiency of % 54 %f or C 2+ pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 52 publications
0
53
0
Order By: Relevance
“…The SEM images in Figures 1 a and b show that the octahedral morphology of HKUST crystals (size of ∼60±20 μm) was well preserved as a template even after the long‐term carbonization process (size of ∼15±5 μm); this is consistent with results from literature. [ 22 , 23 ] A higher magnification view of one of these octahedral microparticles revealed that each octahedron microparticle consisted of ∼80±20 nm spherically shaped CuNPs (Figures 1 c and S3). A more detailed investigation of the structural properties was performed by transmission electron microscopy (TEM) to characterize the composition of individual CuNPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEM images in Figures 1 a and b show that the octahedral morphology of HKUST crystals (size of ∼60±20 μm) was well preserved as a template even after the long‐term carbonization process (size of ∼15±5 μm); this is consistent with results from literature. [ 22 , 23 ] A higher magnification view of one of these octahedral microparticles revealed that each octahedron microparticle consisted of ∼80±20 nm spherically shaped CuNPs (Figures 1 c and S3). A more detailed investigation of the structural properties was performed by transmission electron microscopy (TEM) to characterize the composition of individual CuNPs.…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to the absence of a large carbon matrix, which generally contributes to micro/macroporosity during pyrolysis (Figure S5). [23] …”
Section: Resultsmentioning
confidence: 99%
“…Main eCO 2 RR products were identified as CO at low current density and C 2 H 4 at high current density. For the NH 2 -Cu-BDC and OH-Cu-BDC [2,12,[27][28][29][30][31][32][33] (Table S1, Supporting Information). Black square for the results in the literature.…”
Section: Eco2rr Performance Evaluation Of X-cu-bdcmentioning
confidence: 99%
“…2F-Cu-BDC ranks high in the comparison with the prior best results in literature. [2,12,[27][28][29][30][31][32][33] It also should be noted that although a few catalysts exhibit high R C2/C1 (such as ref. [ 33 ]), their current densities are impractical (<15 mA cm -2 ).…”
Section: Eco2rr Performance Evaluation Of X-cu-bdcmentioning
confidence: 99%
See 1 more Smart Citation